Occupational risk factors impact on the reproductive system of female flight attendants in civil aviation (literature review) - A. R. Dmitrenko; Yu. L. Timoshkova; T. E. Kurmanbaev (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The review article discusses the issues of studying occupational factors on the reproductive health of female flight attendants. The purpose of the study is to identify a correlation between reproductive health disorders of flight attendants and flight factors. Literature data from the Fundamental Library of the Military Medical Academy named after S.M. Kirov, online sci-hub library «CyberLeninka», e-library and PubMed was analyzed and systematized. Such professional factors as: ionizing radiation, physical stress in flight, work in a plantigrade position, disturbance of the regime of working, resting time and eating patterns, constant change of climatic zones, desynchronosis, – were identified. An analysis of the literature has shown that a number of issues related to flight factors and women's health remain poorly understood. It is advisable to study in detail the flight factors: vibration, noise, acceleration, hypoxia, pressure drops, and their impact on the reproductive system of female specialists working in aviation.